Pigmented median raphe cyst of the penis that developed after middle age without infection or trauma history. Issue 3 (4th March 2021) - Kii, Toshihiko; Taguchi, Satoru; Nagahama, Kiyotaka; Shimoyamada, Hiroaki; Honda, Kazuki; Tomida, Yoshihiro; Matsumoto, Ryuki; Kitamura, Junji; Ninomiya, Naoki; Masuda, Kazuki; Nakamura, Yu; Yamaguchi, Tsuyoshi; et al.
Abstract : Introduction: Median raphe cysts are rare benign lesions of the male genitalia that can develop anywhere along the midline from meatus to anus. They are believed to be caused by a defect in closure of median raphe during embryonic development. These cysts commonly appear in childhood or adolescence, although some are diagnosed after middle age, typically triggered by infection or trauma. Pigmented median raphe cysts, or those containing melanin pigment and/or melanocytes, are extremely rare. Case presentation: A 78‐year‐old man visited our hospital with a complaint of a penile mass that he first noticed in his 50s which slowly grew, eventually causing voiding difficulty. He had no history of infection or trauma. The lesion was excised, and the pathological diagnosis was pigmented median raphe cyst. Conclusion: We successfully treated a rare case of pigmented median raphe cyst of the penis that developed after middle age without infection or trauma history.